Analysis of the Implementation of the Work Plan and Budget Year 2023 Towards the Value of Budget Performance Evaluation at Surabaya State University - Sari, Tri Diana; Susilawati, Nuri; Wahyudi, Teguh; Hayati, Masita Nur (Technium Business and Management, 2024)
Universitas Negeri Surabaya (UNESA) has been designated as a Legal Entity State University (PTN BH) that manages academic and non-academic activities autonomously, in accordance with Government Regulation of the Republic of Indonesia number 37 of 2022. In line with this mandate, UNESA needs to develop an effective and accountable Annual Work Plan and Budget (RKAT) to ensure optimal governance and performance achievement. However, the Budget Performance Evaluation (EKA) of the RKAT implementation shows a gap between the budget absorbed and the resulting output achievements. This research aims to analyse the implementation of the 2023 RKAT against the EKA score at UNESA in order to identify constraints and propose improvements in budget management. The research method used was descriptive qualitative, by collecting and analysing qualitative data describing phenomena related to budget implementation in 44 faculties/work units at UNESA. The results showed that 45.45% of the faculties/work units had EKA scores in the good category, while the rest were in the fair, poor, and very poor categories, with an average EKA score of 74.54 or the fair category. The findings suggest that optimising the monitoring and evaluation process, as well as adjusting the indicators and output targets in the RKAT, are needed to improve the budget performance of faculties/work units at UNESA.